2008
DOI: 10.1007/s11095-008-9703-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of PEPT1 Contribution to Oral Absorption of Cephalexin in Rats

Abstract: PEPT1 substantially contributes to oral absorption of cephalexin, around a half of total absorption. However, the function of PEPT1 can be compensated by passive diffusion for cephalexin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 54 publications
3
12
1
Order By: Relevance
“…By maintaining sufficient contact with epithelial cells of the duodenum, jejunum, and ileum, the passive absorption of GlySar may be increased in Pept1 knockout mice, thereby diminishing the "apparent" role of intestinal PEPT1 in drug absorption. Although speculative, this reasoning is in agreement with the findings of Hironaka et al (2009), who reported that PEPT1 contributed to one-half of the total absorption of cephalexin. These authors also noted that, during simulation studies, an 83% bioavailability would be expected for cephalexin in the absence of PEPT1 function because of a compensatory passive diffusion.…”
Section: In Vivo Oral Absorption and Disposition Of Glycylsarcosinesupporting
confidence: 91%
“…By maintaining sufficient contact with epithelial cells of the duodenum, jejunum, and ileum, the passive absorption of GlySar may be increased in Pept1 knockout mice, thereby diminishing the "apparent" role of intestinal PEPT1 in drug absorption. Although speculative, this reasoning is in agreement with the findings of Hironaka et al (2009), who reported that PEPT1 contributed to one-half of the total absorption of cephalexin. These authors also noted that, during simulation studies, an 83% bioavailability would be expected for cephalexin in the absence of PEPT1 function because of a compensatory passive diffusion.…”
Section: In Vivo Oral Absorption and Disposition Of Glycylsarcosinesupporting
confidence: 91%
“…[266,267]) have been carried out on SLC15 [268] members (previously known as PEPT1 and PEPT2), and responsible e.g. for the intestinal uptake of penicillins [269] and cepaholsporins [270,271].…”
Section: The Importance Of Qsars (Quantitative Structure-activity Relmentioning
confidence: 99%
“…We used jejunum region in this study, because the intestinal absorption of cephalexin was site dependent, which is much higher in the upper segment of small intestine than that in the lower segment. 20,21) As shown in Fig. 3, no significant difference in the intestinal transport of cephalexin was observed in the presence of Wellsolve as compared with the control, although there was a slight increase in the transport of cephalexin with the concentration of 1%, 5% and 10% (v/v) Wellsolve.…”
Section: Effect Of Wellsolve On the Transport Of Cf Across The Intestmentioning
confidence: 78%